The Effect of Price, Trust, and Product Quality on Purchase Decisions Using Tokopedia E-Commerce (Case Study of Students of Riau Islamic University) - Uchi Leli Syahputri; Syahdanur Syahdanur (Majapahit Journal of Islamic Finance and Management, 2025)
The purpose of this study is to determine and analyze the influence of price, trust, and product quality on purchasing decisions using Tokopedia e-commerce among students of the Islamic University of Riau. The population in this study were students of the Islamic University of Riau who purchased products on Tokopedia e-commerce, sample determination was carried out using the Purposive sampling method. Therefore, the sample used in this study was 100 consumers. Data collection techniques in this study used questionnaires, interviews, and documentation. Data analysis used in this study involved testing and analysis in the form of numbers and concluding the results of the test in the study. The results showed that partially the variables Price (X1), Trust (X2), and Product Quality (X3) had a significant influence on purchasing decisions in purchasing products on Tokopedia e-commerce. The magnitude of the influence of price, trust, and product quality on this purchasing decision was with an R Square value of 0.666%.